Theoretical Aspects Of Manager And Management Personnel - Atamuratov Murat Utepbergenovich (International Journal of Advanced Science and Technology, 2020)
The article analyzes the theoretical aspects of the views of Eastern and Western scholars on manager and management personnel. At the new stage of development of Uzbekistan, the new requirements for manager and management personnel and its scientific and theoretical aspects were studied in connection with the problems facing society and relevant conclusions were given.